Voluntary Corporate Climate Initiatives and Regulatory Loom: Batten Down the Hatches - Dragan Ilic; Janick Christian Mollet (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
The rationale of voluntary corporate initiatives is often explained with anticipation of future regulation. We test this hypothesis for the Chicago Climate Exchange (CCX) and the Climate Leaders (CL), two popular voluntary US environmental programs to curb carbon emission that were operating during a decisive regulatory event. In 2009 the Waxman-Markey Bill surprisingly passed the House of Representatives and brought the US economy a big step closer to a nationwide CO2 emission trading system. In an event study we assess how the stock market adjusted prices when the likelihood of CO2 regulation unexpectedly increased. We develop a simple model to investigate the empirical results. Our findings suggest that only membership in the CCX was considered beneficial, an initiative whose market oriented design happened to dovetail with the bill's. Earlier stock market reactions to membership announcements in these voluntary programs paint a complementary picture. But membership alone cannot account for the entire price adjustments. Our results show that a substantial part of the market reaction can be traced back to industry-wide effects.
Keywords: G38; Q53; Q54; Q58; 330; Voluntary markets; permit markets; climate change; greenhouse gas emissions; CO2; corporate social responsibility; shareholder wealth; Klimawandel; Internationale Umweltpolitik; Grenzüberschreitende Umweltbelastung; Treibhausgas-Emissionen; Sozialethik; Corporate Social Responsibility; Selbstverpflichtung; Umweltschutz